Pengaruh Penggunaan Media Manipulatif Terhadap Kemampuan Mengenal Konsep Bilangan Pada Anak Usia Dini di TK Kartini Nagrak Selatan Sukabumi - Aeni Latifah; Muhammad Iqbalullah; Eki Agustin (Institut Madani Nusantara, 2021)
The purpose of this study was to determine the initial ability to recognize the concept of numbers in early childhood in the control group and in the experimental group before using manipulative media and to determine the final ability to recognize the concept of numbers in children aged in the control group and in the experimental group after using manipulative media and to find out whether there is a significant effect on the ability to recognize number concepts in early childhood in the control group and the experimental group before and after being given manipulative media. The research method used was a quasi-experimental. This quasi-experimental method was carried out because the researchers did not form a random class with children, thus the experiment was carried out on existing classes. The results showed that there was a significant effect on the ability to recognize the concept of numbers in early childhood. This was proven from the average value of the experimental group pre-test 20.8000 changed to 37.7000 at the time of post-test, while in the control group pre-test 19.4545 changed to 22.6364 at the time of post-test. This proves that the manipulative media treatment applied can have an effect on the ability to recognize the concept of numbers for early childhood.